Endless Visions, Virtual Desires, and Broadcasted Emotions. Frederick Kiesler’s Architectures of Immersion (Cinéma & Cie. Film and Media Studies Journal, 2023)
The article aims to investigate the salient features of Frederick Kiesler oeuvre – the theatrical mise-en-scene as a multimedia display, the dramatization of the space of consumption and the space of the art exhibition for immersive purposes, cinema understood as a totalizing and spiritual experience, and the intuition of a virtualized, individual and domestic experience of the artwork – through the analysis of a selection of his projects, in light of the most recent categories proposed for the investigation of immersivity. The purpose of this study is to place Kiesler’s work in a mediaarchaeological perspective that takes into account the constant and fruitful asynchrony with the media present in which his work is historically situated.
Keywords: Frederick Kiesler; Environment; Immersivity; Display